Dataset for paper: The impact of some sunscreens on local sweating differs in men and women during exercise in the heat - Garzón Mosquera, Julián Camilo (2024)
Sunscreens may affect thermoregulation and sweating during exercise in warm climates. In this study, we compared the effects of three sunscreens on local sweating rate (LSR) during exercise under controlled conditions (32 °C, RH rh 55%). Fifteen subjects (8 men, 7 women) underwent 20-min cycles in 4 randomized treatments: control (CON), sunscreen A (organicSSA), sunscreen B (SSB) and sunscreen C (inorganicSSC). LSR was measured by a patch on the scapular region. This dataset includes all the data used for the publication with the same title, currently under review.